O texto, o contexto e o pretexto : ensino de literatura, após a reforma do ensino médio - Cabral, Ana Beatriz (Universidade Federal de São Carlos, 2008)
The secundary educational reform in Brazil grants to secondary school the role of improving knowledge acquired on previous education level in order to offer students conditions of pursuit on superior education, as well it imputs responsibility on this level for giving students work basic skills and also to prepare them for citizenship. The new rules for secondary education are also defined by two others documents, the Diretrizes Curriculares Nacionais do Ensino Médio and Parâmetros Curriculares Nacionais do Ensino Médio, which present the philosophical and curricular principles that guide the reform and also provide basic competences that students must develop in this school level. Based on these documents and considering that the reform removed from the secundary level curriculum the Literature as a knowledge field, this research investigates the Literature teaching after the secondary educational reform, through the path of three theoretical fields: the Literature teaching, the secundary reform as a public state policy and the teachers knowlegde and practices. To achieve this purpose, there were selected Brasilia s public and private schools by the scores they got in Exame Nacional do Ensino Médio of 2005. Then 38 teachers from these schools fulfilled a semistructured questionnaire and two teachers were interviewed. In order to inquire this material, the theoretical fields and the field research put together alowed us to know the profile of well succeeded Literature teachers from Distrito Federal, their pedagogical practices and knowledge and yet how this knowledge meets the reform framework. All that provide a panorama of the Literature teaching after the secundary educational reform in the Distrito Federal.
Keywords: Ensino médio; Literatura; Reforma do ensino; Avaliação; Texto literário; Políticas públicas de educação; Formação de Professores; Práticas pedagógicas e saberes docentes; Public education policies; Secundary educational reform; Literature teaching; Teachers training and pedagogical practices and knowledge; CIENCIAS HUMANAS::EDUCACAO